Natural Killer Cells and Their Role in Rheumatoid Arthritis: Friend or Foe? - Hamid Shegarfi; Fatemeh Naddafi; Abbas Mirshafiey (The Scientific World Journal)
Rheumatoid arthritis (RA) is a long-term disease that leads to inflammation of the joints and surrounding tissues. Natural killer (NK) cells are an important part of the innate immune system and are responsible for the first line of defense against pathogens during the initial immune challenge before the adaptive immune system eventually eliminates the infectious burden. NK cells have the capacity to damage normal cells or through interaction with other cells such as dendritic cells, macrophages, and T cells cause autoimmune diseases, such as RA. NK cells isolated from the joints of patients with RA suggest that they may play a role in this disease. However, the involvement of NK cells in RA pathology is not fully elucidated. Both protective and detrimental roles of NK cells in RA have recently been reported. A better understanding of NK cells' role in RA might help to develop new therapeutic strategies for treatment of the RA or other autoimmune diseases. We have decided in this paper to focus on the NK cell biology, and attempt to bring the interested readership of this Journal up to date on the NK cell, specifically its possible relation to RA.